‘Attend you and give ear a while...’ singing about the naval, the imperial-national and the local in 18th century Bristol - Karampoulas, Vasilis (Mos Historicus: A Critical Review of European History, 2025)
The Royal Navy constituted one of the core pillars of the British Empire’s expansion, supporting its domination on the seas and concurrently fuelling the imagination of its populace. This article analyses the stereotype that emerged during the first half of the 18th century through the study of a popular media of communication of the period: ballads. By focusing on the case of Bristol, the analysis examines sailor ballads with a Bristol orientation, thereby showcasing the types of “seamen” that emerged during this time, the underlying hierarchies that define them, and the ideologies they promote. By examining the social and cultural dimensions of the British Empire’s ideology and the networks through which the ballads were disseminated, the study argues that the “stereotypes” perpetuated by these ballads serve as “cultural” link between the local and the imperial national.